PENGARUH STAD TERHADAP HASIL BELAJAR DITINJAU DARI MOTIVASI BELAJAR SISWA - Rosalia Marselina Olinan; Sigit Sujatmika (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2017)
The purpose of this research is to know the tendency of science learning result of VII students of SMP Taman Dewasa Jetis Yogyakarta in academic year 2016/2017 which study using STAD type cooperative learning model (achievement model achievement), direct learning model, and student learning motivation. The object of this study is the result of learning science IPA students. The type of this research is Quasi Eksperimen. The data was collected by using documentation technique to know the students 'initial ability, questionnaire technique to know the students' learning motivation, and the test technique to know the learning result of the science student. The test instrument is about multiple choice questions 30 questions, and positive and negative questionnaire instruments. The results obtained f= 1.596 with p = 0.140 and the result of learning achievement equal to 19,83, mean of the result of questionnaire equal to 74,22. Based on the average of learning outcomes and the results of questionnaires, then there is the influence of the use of STAD type cooperative learning model on the learning outcomes of science students of class VII in review of student learning motivation.